The Influence of Employee Engagement and Digital Skills on the Performance of Generation Z Employees in MSMEs in West Lombok Regency - Regina Rendisti Pratiwi Pratiwi; Agusdin Agusdin (Amkop Management Accounting Review (AMAR), 2026)
Digital transformation in the MSME sector requires employees to have good work engagement and digital skills to be able to increase work productivity. This study aims to analyze the effect of employee engagement and digital skills on the performance of Generation Z employees in MSMEs in West Lombok Regency. The study used a quantitative approach with a causal associative method. The study population was 34,081 MSMEs in West Lombok Regency, with a sample of 100 respondents selected using a purposive sampling technique. Data were collected through a Likert scale questionnaire, observation, interviews, and documentation. Data analysis was carried out using SPSS through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that digital skills had a positive and significant effect on employee performance, while employee engagement had no significant effect partially. In addition, employee engagement and digital skills simultaneously had a significant effect on employee performance with an Adjusted R Square value of 72.9%. The conclusion of the study shows that digital skills are a dominant factor in improving the performance of Generation Z employees in MSMEs in the digital era.